Exploring the perspectives of bullying amongst Grade 5 girls - Bredekamp, Judith; Swart, Estelle (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MEd (Educational Psychology))--University of Stellenbosch, 2007.